Fe Ion extraction in patchouli oil with ion exchange using resin - Jaenuri, Abdul Rahman Khadafi; Anarchie, Thafie Ghilas; Sumada, Ketut (Fakultas Teknik Universitas Brawijaya, 2023)
Patchouli is the largest non-oil export commodity among essential oil exports in Indonesia. However, the quality of patchouli oil in Indonesia is considered to be very low. Traditional patchouli oil distillation is carried out in a small capacity and uses a simple distillation method based on a large difference in boiling points or one of the volatile components. This process produces poor quality patchouli oil such as acid number more than 8, dark oil, patchouli alcohol less than 30%, and high water content. This is evidenced by the large amount of Fe metal contained in patchouli oil. Patchouli oil produced contains a lot of iron in its yield, so it needs further processing to reduce the Fe content in patchouli oil. The use of resin as an adsorbent for Fe metal is one way to reduce the Fe metal content. Resin weighing 50, 150 and 250 grams was added to 200 ml of patchouli oil. Then the stirring process was carried out with a stirring speed of 200 rpm with time variations of 30, 60 and 90 minutes. The results obtained showed the best adsorption process with Fe content in patchouli oil of 1.42 mg/Kg, contact time of 90 minutes and amount of resin of 250 grams with the largest percentage of removal of 87.5%. Keywords: Patchouli oil, Ion Exchange, Resin.